FAKTOR –FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK WAJIB PAJAK ORANG PRIBADI - Fibria Anggraini P.L (Universitas Indraprasta PGRI, 2015)
The purpose of this study was to analyze the factors that affect tax compliance (tax compliance) individual taxpayers This study uses the variable individual behavior, motivation and organizational climate as the independent variable and tax compliance individual taxpayers as the dependent variable. Data analysis was performed using multiple linear regression analysis with SPSS for Windows Version 19.00. The results of this study indicate that individual behavior, motivation and organizational climate have significant effect on tax compliance individual taxpayers . Keywords: individual behavior, motivation, organizational climate, tax compliance.